Answer:
![y+3=-6(x+9)](https://tex.z-dn.net/?f=y%2B3%3D-6%28x%2B9%29)
Step-by-step explanation:
We are given that
Slope of a line=-6
Given point =(-9,-3)
We have to find the equation which represents the line.
The equation of line passing through the given point
with slope m is given by
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
Substitute the values then we get
The equation of line passing through the point (-9,-3) with slope -6 is given by
![y-(-3)=-6(x-(-9))](https://tex.z-dn.net/?f=y-%28-3%29%3D-6%28x-%28-9%29%29)
![y+3=-6(x+9)](https://tex.z-dn.net/?f=y%2B3%3D-6%28x%2B9%29)
Hence, the equation of line that passes through (-9,-3) and has a slope -6 is given by
![y+3=-6(x+9)](https://tex.z-dn.net/?f=y%2B3%3D-6%28x%2B9%29)